The new tenant - Ionesco, Eugène.; Encyclopaedia Britannica Educational Corporation (Chicago : Encyclopaedia Britannica Educational Corp., 1975)
Presents an adaptation of the Ionesco play about a man moving into a room in a city.
Director, Larry Yust.
Paul Schumacher, Eve McVeagh, Carl Byrd, John Crawford.
Keywords: Short films